Decoloniality, language and literacy: conversations with teacher educators Edited by Carolyn Mckinney and Pam Christie - Hiss, Amy (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The book offers a view on the role of teacher educators as transformation agents of language and literacy practices in South African classrooms and PGCE/teaching programmes. The book explores the way in which the authors themselves as teacher educators/facilitators and researchers show how multilingualism and multiliteracies can be curated by working with different modalities and exposure to different school spaces across the economic spectrum in South Africa. The book offers a view on how teacher educators and pre- service teachers can build collaborative relationships with each other in developing creative ways in which their own positioning and knowledge aid in developing linguistically rich learning environments, breaking down the status quo of coloniality in education. Through the perspective of ‘third’ spaces (Guiterrez, 2008) the authors demonstrate ways in which pluriversality (Mignolo, 2013) can emerge through collaborative language practices in the classroom, which by and large paves the way for decolonised education in South Africa.